2018
DOI: 10.1016/j.ribaf.2017.07.100
|View full text |Cite
|
Sign up to set email alerts
|

The impact of monetary policy on gold price dynamics

Abstract: Ever since the collapse of the Bretton-Woods system, gold has retained its function as an important monetary commodity (Baur and Lucey, 2010), and continues to provide important inflation forecasting information to monetary policy setters (Tkacz, 2007). However, Capie et al. (2005) highlight the instability of gold price dynamics through time, attributing it to unpredictable political attitudes and events. In this paper, we investigate gold price dynamics under different inflation regimes and stock market cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…The period of interest Q2, 2000 to Q3, 2017 was characterized by the global financial crisis that saw several states look to monetary policy (increased liquidity of financial institutions) as a solution, from which, stems our consideration of quantitative easing. As the literature suggests, the impact of QE on the gold price has received little attention, with the most noticeable exception being that of Zhu, et al (2018), in which an event-study analysis of the impact of QE announcements was conducted. It is worth noting that this study is however, not primarily concerned with QE announcements (which has short run effects), but rather deliberated on actual QE.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The period of interest Q2, 2000 to Q3, 2017 was characterized by the global financial crisis that saw several states look to monetary policy (increased liquidity of financial institutions) as a solution, from which, stems our consideration of quantitative easing. As the literature suggests, the impact of QE on the gold price has received little attention, with the most noticeable exception being that of Zhu, et al (2018), in which an event-study analysis of the impact of QE announcements was conducted. It is worth noting that this study is however, not primarily concerned with QE announcements (which has short run effects), but rather deliberated on actual QE.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas Batten, Ciner and Lucey (2010) found that between 1985 to 2012, there was no correlation between gold and the US CPI viii . The ambiguous relationship was best summarized and put into context by Zhu, Fan and Tucker (2018), who asserted that "once investors take into account the transaction costs associated with buying and selling of gold, they may decide that trading in gold is not worthwhile, and will stop treating gold as an inflation hedge".…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gold is a kind of precious metal, and its ductility is the highest among the known metals. In modern life, gold is mainly used for international reserves, jewelry decoration, industrial, science, and technology application [1][2][3]. In some countries, gold is the standard for currency trading and used for making coins and jewelry.…”
Section: Introductionmentioning
confidence: 99%